Bioengineering of plant (tri)terpenoids: from metabolic engineering of plants to synthetic biology in vivo and in vitro. Issue 1 (14th May 2013) - Moses, Tessa; Pollier, Jacob; Thevelein, Johan M.; Goossens, Alain
Summary Terpenoids constitute a large and diverse class of natural products that serve many functions in nature. Most of the tens of thousands of the discovered terpenoids are synthesized by plants, where they function as primary metabolites involved in growth and development, or as secondary metabolites that optimize the interaction between the plant and its environment. Several plant terpenoids are economically important molecules that serve many applications as pharmaceuticals, pesticides, etc. Major challenges for the commercialization of plant‐derived terpenoids include their low production levels in planta and the continuous demand of industry for novel molecules with new or superior biological activities. Here, we highlight several synthetic biology methods to enhance and diversify the production of plant terpenoids, with a foresight towards triterpenoid engineering, the least engineered class of bioactive terpenoids. Increased or cheaper production of valuable triterpenoids may be obtained by 'classic' metabolic engineering of plants or by heterologous production of the compounds in other plants or microbes. Novel triterpenoid structures can be generated through combinatorial biosynthesis or directed enzyme evolution approaches. In its ultimate form, synthetic biology may lead to the production of large amounts of plant triterpenoids in in vitro systems or custom‐designed artificial biological systems.